Comparison of Satisfaction Level of Customers between Public and Private Commercial Banks in Kathmandu Valley - Khanal, Kapil (Management Dynamics, 2018)
The intention of the study was to identify the various important service quality dimensions in commercial banking industry in Kathmandu valley. Data was collected through questionnaire and this questionnaire was distributed among 240 customers of 28 commercial banks. Random sampling technique was used in this procedure. Arithmetic means, standard deviation and factor analysis were used to analyze and interpret data. It has been found that customer of public sector bank perceived highest value in assurance dimension, like safety in transaction and consistency in services. The Research has revealed that the highest Eigen value (7.486) in Reliability dimension. There exists a positive relation overall and boost job satisfaction, which would in turn enhance the productivity of the organization.